2019
DOI: 10.1111/dme.13905
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the severity of Type 2 diabetes using clinical data‐based measures: a systematic review

Abstract: Aims To identify and critically appraise measures that use clinical data to grade the severity of Type 2 diabetes. Methods We searched MEDLINE, Embase and PubMed between inception and June 2018. Studies reporting on clinical data-based diabetes-specific severity measures in adults with Type 2 diabetes were included. We excluded studies conducted solely in participants with other types of diabetes. After independent screening, the characteristics of the eligible measures including design and severity domains, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Section C contains medical/health variables, such as ABO blood groups, rhesus blood groups, and the severity of T2DM among various blood groups. The severity of DM was scored based on the number of diabetes-related complications and frequency of hospital visits (Zghebi et al 2019). DM was considered severe if the patient had at least one diabetes-related complication and visited the hospital monthly.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…Section C contains medical/health variables, such as ABO blood groups, rhesus blood groups, and the severity of T2DM among various blood groups. The severity of DM was scored based on the number of diabetes-related complications and frequency of hospital visits (Zghebi et al 2019). DM was considered severe if the patient had at least one diabetes-related complication and visited the hospital monthly.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…aim 1: diabetes severity assessment Severity domains Key clinically relevant indicators of type 2 diabetes severity (severity domains) were identified from a systematic review of studies that quantified type 2 diabetes severity. 14 We also sought expert clinical opinion in cardiology, diabetes and primary care, supplementing the list of severity domains. HbA 1c and demographic variables were excluded from the severity domains.…”
Section: Research Design and Methods Data Source And Patient Populationmentioning
confidence: 99%
“…Our recent systematic review found that a few studies have assessed or quantified disease severity among individuals with type 2 diabetes and fewer had useful longitudinal measures. [11][12][13][14] We identified the need for a valid and reliable tool for measuring severity of type 2 diabetes and that can serve as an actionable tool for therapeutic targets, as a covariate in epidemiological research, and for stratifying populations in order to inform resource allocation and support commissioning and public health programs for people with diabetes. 7 Our study aimed to (1) develop a type 2 diabetes severity score (the DIabetes Severity SCOre, DISSCO), (2) evaluate the association and the added clinical utility of the severity score in predicting hospitalization and mortality outcomes beyond that achieved using models incorporating sociodemographic variables and HbA 1c , and (3) validate DISSCO using a separate cohort (validation data set).…”
mentioning
confidence: 99%
“…Assessing diabetes severity is important and could help identify people in need of targeted therapies and healthcare services 8 10 . Here, the severity of diabetes refers to diabetes duration, treatment status, and diabetes complications.…”
Section: Introductionmentioning
confidence: 99%